Islamic Theological Study of Empowerment Scavenger Community in Cultivating Nature Plastic Waste Becomes Valuable - Kadir, Surni sr; Nuranisa, Nuranisa; Kamal, Kamal (LP2M of Institute for Research and Community Services - UIN Walisongo, 2024)
This article explores the perspective of Islamic theology related to the empowerment of scavenger communities in waste management, especially plastic waste, to increase economic and environmental value. This article also examines the basic principles of Islamic teachings on the environment, social responsibility, and sustainability, and their application in the context of waste management by scavengers. Through literature analysis and case studies, this article identifies the potential for integrating Islamic values with community empowerment practices in waste management through handicrafts made from plastic waste, so that waste that has been considered useless can provide added value for scavengers. The method used is PAR, a method that involves active participation from the scavenger community in every stage of research and development of solutions to overcome their problems. The results of this research are that the first returnee community is given knowledge and skills to process waste, especially plastic waste into valuable handicraft products in the form of Bag and Wallet accessories of various models and shapes. Second, that Islamic teachings that emphasize concern for the environment and community welfare can be a strong foundation for scavenger empowerment programs, including skills training, access to recycling technology, and strengthening social networks. Thus, the Islamic theological approach has the potential to increase the effectiveness and sustainability of waste management efforts, as well as provide economic and social benefits for the scavenger community.